Philippines : Report on Observance of Standards and Codes-Payment Systems. (IMF Staff Country Reports; Country Report, 2005)
This Report evaluates the Observance of Standards and Codes on the Payment Systems for the Philippines. The assessment confirms that the infrastructure for effective supervision has improved considerably in recent years. Although important gaps exist, compliance is overall quite high. The weaknesses that exist are, however, critical and derive in part from a supervisory structure and its enforcement capacities being out of line with key challenges. Among these are the needs to reorient the framework away from forbearance and liquidity support to one that is based on early problem identification, prompt corrective action, and resolution.